2015
DOI: 10.1111/1759-7714.12287
|View full text |Cite
|
Sign up to set email alerts
|

China national lung cancer screening guideline with low‐dose computed tomography (2015 version)

Abstract: BackgroundLung cancer is the leading cause of cancer-related death in China. Results from a randomized controlled trial using annual low-dose computed tomography (LDCT) in specific high-risk groups demonstrated a 20% reduction in lung cancer mortality.MethodsA China national lung cancer screening guideline was developed by lung cancer early detection and treatment expert group appointed by the National Health and Family Planning Commission, based on results of the National Lung Screening Trial, systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 35 publications
(33 reference statements)
1
104
0
1
Order By: Relevance
“…In the United States, the National Lung Screening Trial showed 16‐20% fewer lung cancer deaths among current or former heavy or long‐term smokers (30 pack‐years) who were screened with low‐dose chest CT as opposed to standard chest x‐ray . Annual low‐dose chest CT is the current lung cancer screening recommendation for smokers or former smokers age 55‐74 in several countries including United States, China, and Europe (smoking history indication varies by country) . However, there is uncertainty about the potential harms of screening and generalizability of results which has led to further studies on biomarkers of lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the National Lung Screening Trial showed 16‐20% fewer lung cancer deaths among current or former heavy or long‐term smokers (30 pack‐years) who were screened with low‐dose chest CT as opposed to standard chest x‐ray . Annual low‐dose chest CT is the current lung cancer screening recommendation for smokers or former smokers age 55‐74 in several countries including United States, China, and Europe (smoking history indication varies by country) . However, there is uncertainty about the potential harms of screening and generalizability of results which has led to further studies on biomarkers of lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…However, 20% of these patients were finally shown to be noninvasive lesions by postoperative pathological diagnosis. Currently, LDCT screening is recommended as an efficient method for the early detection of lung cancer in China [25], with a high sensitivity to detect small pulmonary nodules, even those less than 10 mm in diameter. However, because there is considerable overlap among the imaging features of AAH, AIS, and IA, it is challenging to differentiate noninvasive from invasive nodules by a visual assessment of morphological characteristics based on CT imaging [8].…”
Section: Discussionmentioning
confidence: 99%
“…[9] Screening based on environmental or occupational exposure was not incorporated into our current model. Many people in China, especially women, are non-smokers, but are still at an increased risk for lung cancer due to heavy exposure to environmental tobacco smoke at work.…”
Section: Discussionmentioning
confidence: 99%